FACTORS AND TRIP PREFERENCE OF ONLINE FOOD DELIVERY USERS IN BANDUNG CITY - Rizal Hendarto, Syamsu
Technology development in the field of information and communication death happened globally.Since the internet, all things be able to connect quickly and real time. The development of information and communication technology marked by the emergence of new startups like Gojek and Grab. One of the service from startups is online food delivery service. A service that allows one to order food and drink through mobile phone (online). Technology development is not without any impacts to people trip patterns. Logically, according to Salomon ( 2008 ) changes in trip patterns have the potential to change land use and location selection decisions. However, after observing and interviewing several restaurants/cafes in the city of Bandung, the phenomenon of land use change what predicted by urban experts has not yet occurred. Based on this, a new thought, before finding out the changes in the land use pattern, it is necessary to know first about factors and trip preference online food delivery user in Bandung City. The possible forms of trip preferences that appear are substitution, complementary, modification, and neutral (Salomon, 1985). The analytical method used is the content analysis of the literature to determine the factors that influence online buying behavior. Descriptive analysis method is used to describe the characteristics of online food delivery service users and the trip preferences of users of these services in the city of Bandung. To find out the multivariate effect between the variables of the factors that influence the behavior of using online food delivery services, a logistic regression analysis method is used. The results of the analysis that have been carried out are groups of sociodemographic, spatial, and individual habits/behaviors that are still feasible to predict the behavior of using online food delivery services. While the relationship that occurs between these online services and user trip preferences is complementary and modified. If combined, the people of Bandung City who use these services tend to review the restaurant/cafe that they want to visit through the application, then they come to him directly. It can be concluded that the presence of online food delivery services instead of reducing travel, actually adds to the number of movements.